Establishing Academic Burnout’s Relationship with Problematic Internet Use and Specific Health-Risk Behaviours : A Cross-sectional Study of Finnish Higher Education Students - Männikkö, Niko (Springer, 2025)
Problematic Internet use is recognised as an emerging public health issue, particularly among young adults. Yet, there is scarce information on problematic Internet use as a predictor for academic burnout. This study aimed to identify academic burnout’s association with both problematic Internet use and specific health-risk behaviour among higher education students. We analysed the population-based cross-sectional survey data (with post-stratification weighting) of Finnish higher education students. Data was collected in 2021 (n = 6258; age 18–34). Regression analyses were used to investigate academic burnout’s relationship with problematic Internet use and health-risk behaviours. The results revealed that female gender, learning difficulties, the use snus (the Swedish-type of moist snuff), problematic Internet use, online shopping, and perceived loneliness were significantly and positively associated with academic burnout. In addition, a higher number of study credits earned, self-perceived good health, and a satisfactory financial level were significantly and inversely associated with academic burnout. The findings suggest that screening students for problematic behaviour and offering support for those in need are likely to be effective at increasing academic well-being among higher education students. © The Author(s) 2024.